LncRNAs as tumor cell intrinsic factors that affect cancer immunotherapy - Egranov, Sergey D. (RNA Biol, 2020)
Long noncoding RNAs (lncRNAs) have been found to associate with all major types of malignancies and play important roles in regulating several hallmarks of cancer by interacting with proteins, DNA, and RNA. The possible functions of lncRNAs and their roles in the regulation of tumour growth will be reported and discussed in the present review. In our recent report, based on genetic mice models and a series of systematic analyses, we suggested that lncRNAs also play critical roles in the regulation of antigen presentation in tumour cells and allow tumour cells to escape immune surveillance, which further broadens the scope of understanding lncRNA functions and how they relate to cancer immunotherapy resistance.